Assessment of genetic variability of passion fruit using simple sequence repeat (SSR) markers - Chepkoech, Emmy; Rotich, Felix; Alkamoi, Bonface (Integrity, 2020)
Purple passion fruit (Passiflora edulis Sims) is the third most important fruit crop in Kenya that is produced for both local and export markets. In Uasin Gishu County, passion fruit had recently emerged as an important cash crop for the small-holder farmers. Understanding the structure and diversity of species is very important in plant breeding and in conservation of genetic resources related activities. This study was set out in 2017-2018 to determine the genetic diversity of purple passion fruits genotypes grown in Uasin Gishu County, Kenya using SSR markers. Among the 50 purple passion fruit accessions used in this study, the genetic distance coefficients among accessions ranged from 0.24 to 0.72, with an average of 0.48. The results of STRUCTURE analysis suggested that the 50 accessions could be grouped into five sub-populations. The clustering was based on the unweighted pair-group method of arithmetic averages (UPGMA) where accessions were divided into three major clusters. The UPGMA dendrogram revealed that accessions from identical or adjacent areas were generally, but not entirely, clustered into the same cluster. Comparison of the UPGMA dendrogram and the Bayesian STRUCTURE analysis showed general agreement between the population sub-divisions and the genetic relationships among accessions. Principal coordinate analysis (PCoA) with SSR markers revealed a similar grouping of accessions to the UPGMA dendrogram and STRUCTURE analysis. Analysis of molecular variance (AMOVA) indicated that 16% of the total was attributed to the diversity among sub-populations, while 84% was associated with differences within sub-populations. Overall, there was a considerable amount of genetic variability among passion fruit accessions grown in Uasin Gishu County of Kenya. The study represents the comprehensive investigation of the genetic diversity of passion fruit accessions which would be valuable for germplasm collection, genetic improvement, and efficient utilization.
Keywords: Accessions; genetic diversity; molecular markers; passion fruit; Uasin Gishu County